Evaluation of air quality and mobility policies in 14 large Italian cities from 2006 to 2016. Issue 7 (6th June 2020) - Tomassetti, Laura; Torre, Marco; Tratzi, Patrizio; Paolini, Valerio; Rizza, Valeria; Segreto, Marco; Petracchini, Francesco
Abstract: Despite a connection between road traffic and air pollution has been clearly identified, few integrated analyses on air quality and mobility policies are currently available worldwide. Aim of this work is to build a framework for the evaluation of the impact of mobility policies on air quality in 14 major Italian cities, on a long-time scale (2006–2016). Air quality data was collected from all PM10, PM2.5, and NO2 monitoring stations, installed in compliance with the European directive 2008/50/EC. A large dataset was collected, including public transport, environmental, and fuel categorization of the private vehicular fleet, low emissions zones and modal split. In the analyzed time period, both public transportation use and private motorization decreased. Considering the environmental classification standards of vehicles, Northern cities are more readily switching to newer and less polluting cars (e.g. Euro 5 and Euro 6). There has been a general reduction in PM and NO2 concentration. Nevertheless, exceedances are still above the targeted limit value, mainly in some Northern cities who made major investments in sustainable and shared mobility: this highlights a strong influence of climatic conditions and other sources. Dramatic variations in the CO/NO ratio were observed in Turin, while smaller changes are observed in Milan, Rome and Palermo.